Of Men and Dogs: An Unpublished Syriac Fairy Tale from the Late Medieval Period - Minov, Sergey (Aramaic studies, 2022)
This article contains the unpublished Syriac text of the Story of the Dog Who Talked. Put down in writing by the West Syrian monk ʿAzīz bar Ṣlīḇā bar Bassūs in the year 1503, the Story is, arguably, the earliest datable specimen of the fairy tale genre of folklore attested in the Syriac language. The text of the Story, published on the basis of manuscript Mardin, Church of the Forty Martyrs, 350, is accompanied by an English translation and discussion.